Bushfire simulators and analysis in Australia: insights into an emerging sociotechnical practice. (27th May 2018) - Neale, Timothy; May, Daniel
ABSTRACT: The present context of escalating environmental risks places increased pressure and importance on our technical ability to predict and mitigate the potential consequences and occurrence of major natural hazards such as bushfire (or 'wildfire'). Over the past decade, bushfire prediction in Australia, as in many other fire-prone countries, has increasingly come to involve both trained fire behaviour analysts and complex computer-based two-dimensional bushfire simulation models. During this transitional moment in bushfire management, there is a clear need to better understand the ways in which such predictive technologies and practitioners influence how we anticipate, encounter and manage this natural hazard and its effects. In this paper, the authors seek to prepare the ground for studies of the social dimensions of bushfire prediction by investigating how simulators and predictive practitioners have been mobilised and represented in Australia to date. The paper concludes by posing several questions that bushfire practitioners, policy-makers and researchers alike in Australia and elsewhere will need to address as our flammable future emerges.